The effect of nursing students’ practice readiness on humanistic practice ability and lifelong learning - Elif Kocaağalar Akince; Gülseren Maraş Baydoğan; Yeliz Sürme; Salime Mucuk (BMC Nursing)
Abstract Background It is thought that nursing students’ readiness for the practice before graduation plays a role in their humanistic practice ability and lifelong learning tendencies. Aim This study was conducted to investigate the effects of senior nursing students’ readiness for the practice on their humanistic practice ability and lifelong learning. Methods Designed as descriptive and correlational.The study was conducted between May and June 2024 among senior nursing students studying in the nursing department of a public university in Turkey in the spring semester of the 2023–2024 academic year. The sample of the study consisted of 287 senior undergraduate nursing students. Data were collected face-to-face survey using Student Identification Form, Casey-Fink Readiness for Practice Scale (CFRPS), Humanistic Practice Ability of Nursing Scale (HPAN) and Lifelong Learning Scale. STROBE checklist followed in this study. Results The students’ practice readiness scale score average was 45.61 ± 5.99, humanistic behavior scale score was 121.21 ± 15.48 and lifelong learning scale score was 118.14 ± 14.00. The mean score of the nursing students’ readiness for practice scale showed significant and moderately positive correlations with feeling ready for the nursing profession (r = 0.445), the humanistic practice ability scale (r = 0.495), and the lifelong learning scale (r = 0.407). It was explained that the best determinants of senior nursing students’ practice readiness were the mean score of feeling ready for the profession, humanistic behavior skill and lifelong learning variables. According to the multiple linear regression model, the variables explain 37% of the total scale scores. Conclusions It was found that nursing students’ readiness for practice was low, and their humanistic care skills and lifelong learning were high.